Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome prevention and transmission liability - Paraguassu, Monica (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: A study on the relationship between the human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) transmission and the need for preventive education and information measures. Objective: To research the references on social reality to guide a preventive-repressive criminal policy aimed at the HIV/AIDS transmission, but able to strengthen the importance of prevention through information and education measures. Methods: A retrospective and prospective interdisciplinary theoretical study, in the field of public health policy and legal-international-criminal-environmental terms, concerning the execution of the perspective of universal human rights considering cultural relativism, the hypothesis of the right to the difference and the peculiarities of the matter of affective-sexual relationships and HIV/AIDS transmission. Results: The importance of preventive measures against the HIV/AIDS transmission through the universalization of health. Conclusion: The need for public policies emphasizing information and educational actions about the disease and its mode of transmission, that is, emphasizing the need of condoms in sexual relations, the co-liability of the person being infected, and the window period in order to avoid criminalization as a solution.